A two‐way road: novel roles for fungal extracellular vesicles. Issue 1 (4th October 2018) - Rodrigues, Marcio L.; Casadevall, Arturo
Summary: The biological functions of fungal extracellular vesicles (EVs) or exosomes have been mostly determined on the basis of the assumption that they are vehicles of trans‐cell wall transport and molecular export. The possibility that fungal cells can bind to and internalize EVs remained largely unaddressed. Recent studies, however, demonstrated that fungal cells can internalize host‐derived and/or fungal EVs through processes that profoundly modify their regular physiology. To illustrate this novel view, we discuss (i) the uptake of plant EVs by phytopathogenic fungi culminating in growth defects and virulence attenuation, (ii) the influence of EV internalization in prion transmission and biofilm formation in yeast cells, and (iii) the EV‐mediated transfer of virulence in isolates of Cryptococcus gattii . These recent observations indicate that the functions exerted by EVs in fungal cells result from previously unknown mechanisms of bidirectional transport, opening new venues for the investigation of how EVs impact fungal physiology. Abstract : The traffic of extracellular vesicles in fungal cells is bidirectional. It has been known for a decade that fungal cells can package molecules inside vesicles for further extracellular release. Recent studies, however, have demonstrated that fungal cells can also internalize extracellular vesicles through processes that result in fundamental biological responses.